2012
DOI: 10.4314/tjpr.v11i3.2
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Evaluation of Glibenclamide-Loaded Biodegradable Nanoparticles

Abstract: Purpose: To formulate and evaluate glibenclamide (GB)-loaded poly (lactic-co-glycolic)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…These outcomes may be attributed to the lower proportion of the polymer with increasing the drug polymer ratio resulted in augmented drug diffusion to the dissolution medium [ 37 ]. These results are in full concordance with those obtained by Behera et al [ 38 ], who prepared glibenclamide NPs and found that the release rate increases by increasing the drug polymer ratio.…”
Section: Discussionsupporting
confidence: 92%
“…These outcomes may be attributed to the lower proportion of the polymer with increasing the drug polymer ratio resulted in augmented drug diffusion to the dissolution medium [ 37 ]. These results are in full concordance with those obtained by Behera et al [ 38 ], who prepared glibenclamide NPs and found that the release rate increases by increasing the drug polymer ratio.…”
Section: Discussionsupporting
confidence: 92%
“…The findings of saturation solubility have been assured with the results of GB release, where only up to 35% of GB has been released from PEG 6000 free GB nanoparticles, while the inclusion of PEG 6000 resulted in the release of 99% of GB. No animal study has been conducted in this research work 72 .…”
Section: H-nano-particlesmentioning
confidence: 99%
“…-Stable dosage forms of drugs which are either unstable (Alai and Lin, 2015;Bhadra et al, 2016) or have unacceptably low bioavailability in nonnanoparticulate dosage forms (Madgulkar et al, 2016;Ramalingam and Ko, 2016). (2) they control and sustain release of the drug during the transportation and at the site of localization (Behera and Sahoo, 2012), altering organ distribution of the drug and subsequent clearance of the drug so as to achieve increase in drug therapeutic efficacy and reduction in side effects (Kadam et al, 2012).…”
Section: The Advantages Of Using Nanoparticles As Drug Delivery System Includementioning
confidence: 99%